2021
DOI: 10.3389/fchem.2021.739791
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Dipeptide Hydrogel: The Structures and Properties

Abstract: Self-assembly peptide-based hydrogels are well known and popular in biomedical applications due to the fact that they are readily controllable and have biocompatibility properties. A dipeptide is the shortest self-assembling motif of peptides. Due to its small size and simple synthesis method, dipeptide can provide a simple and easy-to-use method to study the mechanism of peptides’ self-assembly. This review describes the design and structures of self-assembly linear dipeptide hydrogels. The strategies for pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 127 publications
(154 reference statements)
0
26
0
Order By: Relevance
“…Biocompatible hydrogels result by self-assembling dipeptides (the shortest unit in peptide self-assembling) as a result of coordinated noncovalent interactions by considering molecular (geometry, hydrophobicity, electronics) and environmental (temperature, solvent, light, external forces, etc.) factors [103]. The main chain of dipeptide hydrogelator is obtained by self-assembling via amide bonds and the side chains associate through π-stacking interactions or hydrogen bonds in into viscoelastic fluid or 3D interfacial network under appropriate conditions [104].…”
Section: Biological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocompatible hydrogels result by self-assembling dipeptides (the shortest unit in peptide self-assembling) as a result of coordinated noncovalent interactions by considering molecular (geometry, hydrophobicity, electronics) and environmental (temperature, solvent, light, external forces, etc.) factors [103]. The main chain of dipeptide hydrogelator is obtained by self-assembling via amide bonds and the side chains associate through π-stacking interactions or hydrogen bonds in into viscoelastic fluid or 3D interfacial network under appropriate conditions [104].…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Many efforts were carried out to design and to characterize the performances of polymers and materials by triggering and tuning self-healing behavior, analysis of recovery properties and assessment of healing efficiency [10,12,14,[24][25][26][27][28][29]103,114,146,147,151,152,157,165]. The hydrogels can be used as biomimetic systems for understanding the complex cells behavior to various microenvironments.…”
Section: Self-healing Abilitymentioning
confidence: 99%
“…Considering that the shorter the motif, the lower and easier will be the cost of production, it is thus not surprising that ultra-short peptides are amongst the most attractive supramolecular peptide gelators [46]. In particular, cyclic [47][48][49] or linear dipeptides [50][51][52][53][54][55] are amongst the simplest options as building blocks for hydrogels, however, tripeptides are better positioned for bioactivity. Indeed, it was shown that 25 atoms other than hydrogen constitute the ideal size for drugs and drug-like molecules for maximal ligand-binding efficacy and bioactivity, and this number corresponds to the average number for a tripeptide [56].…”
Section: Self-assembling Short Peptides With Bioactive Motifs For Hyd...mentioning
confidence: 99%
“…[27,75,[78][79][80] The linker segment usually contains amide or urea bonds that not only maintain structural rigidity and conformational flexibility of the gelator but also promote self-assembly through intermolecular hydrogen bonding. [81][82][83][84][85][86] The binding site represents the centre with which the chemical analyte interacts. Depending on the nature of the interactions, broadly two types of approaches are followed in designing the reaction centre.…”
Section: Designing Of Gel-based Sensors: Noncovalent Vs Dosimetric Ap...mentioning
confidence: 99%